2021
DOI: 10.1371/journal.pcbi.1009332
|View full text |Cite
|
Sign up to set email alerts
|

Inter-trial effects in priming of pop-out: Comparison of computational updating models

Abstract: In visual search tasks, repeating features or the position of the target results in faster response times. Such inter-trial ‘priming’ effects occur not just for repetitions from the immediately preceding trial but also from trials further back. A paradigm known to produce particularly long-lasting inter-trial effects–of the target-defining feature, target position, and response (feature)–is the ‘priming of pop-out’ (PoP) paradigm, which typically uses sparse search displays and random swapping across trials of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…We also examined for short-term inter-trial positional-priming effects (e.g., Allenmark et al, 2019, 2021; Sauter et al, 2018) by comparing RT performance across the various inter-trial target distances (Figure 3c). A repeated-measures ANOVA, with the single factor of inter-trial Target Distance, failed to reveal revealed a significant Distance effect, F (4,92) = 1.753, p = .145, , BF incl = .329.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also examined for short-term inter-trial positional-priming effects (e.g., Allenmark et al, 2019, 2021; Sauter et al, 2018) by comparing RT performance across the various inter-trial target distances (Figure 3c). A repeated-measures ANOVA, with the single factor of inter-trial Target Distance, failed to reveal revealed a significant Distance effect, F (4,92) = 1.753, p = .145, , BF incl = .329.…”
Section: Resultsmentioning
confidence: 99%
“…Outliers RTs (slower than 2500 or faster than 200 ms, 6.0%) were again removed prior to further analysis. Similar to Experiment 1a, the error rates were generally low (3.5% of trials) and comparable across the three transitional target location conditions, F(2, 46) = .320, p = .728, = .014, BF incl = .162. 𝜂 We also examined for short-term inter-trial positional-priming effects (e.g., Allenmark et al, 2019Allenmark et al, , 2021Sauter et al, 2018) by comparing RT performance across the various inter-trial target distances (Figure 3c). A repeated-measures ANOVA, with the single factor of inter-trial Target Distance, failed to reveal revealed a significant Distance effect, F(4,92) = 1.753, p = .145, = .071, BF incl = .329 .…”
Section: Error Rates and Mean Rtsmentioning
confidence: 99%
“…Many familiar phenomena belong to the family of selection history effects. For instance, intertrial repetitions of target and distractor features and/or their locations facilitates search on the next trial, known as repetition priming (e.g., Allenmark et al, 2021; Lamy et al, 2008; Maljkovic & Nakayama, 1994). It was shown that priming can make a stimulus appear to be more salient even though it physically had the same salience as the stimulus that was not primed (e.g., Theeuwes & Van der Burg, 2013).…”
mentioning
confidence: 99%
“…2). Most computational studies on understanding selection history effects in an oddity target search experiment (33)(34)(35) have been based on Ratcliff's diffusion model (RDM) (42). RDM conceptualizes decision-making in such visual experiments as a noisy accumulation process of decision-relevant perceptual evidence (e.g., the color), parameterized by the rate of evidence accumulation, the response threshold determining the amount of evidence needed to generate a response, and the bias toward a certain response.…”
Section: Discussionmentioning
confidence: 99%
“…In model 3, we also considered three variants of temporal weightings that combine prior target and distractor features: simultaneous co-contribution (model 3a), facilitation precedes inhibition (model 3b), and inhibition precedes facilitation (model 3c). Note that previous studies, which primarily employed driftdiffusion models, cannot distinguish between these alternative mechanisms because they typically do not consider separate target facilitation and distractor inhibition and primarily focus on perceptual selection history (33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%